2005
DOI: 10.1094/cc-82-0228
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatments of Milled Rice and Properties of the Flours

Abstract: Cereal Chem. 82(2):228-232The effects of autoclave and oven treatments on the gelatinization of rice flour and on the rheological characteristics of its pastes were studied by differential scanning calorimetry (DSC), rapid viscoanalysis (RVA), and rotational viscometry. Flours from autoclave-treated rice (ATR) and oven-treated rice (OTR) were prepared, respectively, by heating at 120°C for 60 min and 160°C for 60 min followed by drying (ATR sample), and grinding at 2.2-12.9% moisture content. The rice flour di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 21 publications
(11 reference statements)
6
26
0
1
Order By: Relevance
“…The subsequent magnification revealed that primarily rough and frayed particle shapes in native flour become more rounded and ovoid (Fig. 3-A2-B2-C2) in treated samples which was also confirmed previously by Takahashi et al (2005) for short grain rice autoclaved at 20% of moisture content. The particles' surface ( Fig.3-A3-B3-C3) appears to be smoother and aligned similar as reported by other researchers for short rice grain flour (Majzoobi et al, 2016) and foxtail millet flour (Amadou et al, 2014) when were submitted to convectional hydrothermal treatments.…”
Section: Morphology Of Samplessupporting
confidence: 87%
“…The subsequent magnification revealed that primarily rough and frayed particle shapes in native flour become more rounded and ovoid (Fig. 3-A2-B2-C2) in treated samples which was also confirmed previously by Takahashi et al (2005) for short grain rice autoclaved at 20% of moisture content. The particles' surface ( Fig.3-A3-B3-C3) appears to be smoother and aligned similar as reported by other researchers for short rice grain flour (Majzoobi et al, 2016) and foxtail millet flour (Amadou et al, 2014) when were submitted to convectional hydrothermal treatments.…”
Section: Morphology Of Samplessupporting
confidence: 87%
“…This may be attributed to the change in colour caused by Maillard reaction between reducing sugar from the heated starch and the amino group in the proteins during modification (Lorlowhakarn and Naivikul 2006). Increased a and b colour values have been reported for japonica milled heat moisture treated rice flour (Takahashi et al 2005).…”
Section: Colourmentioning
confidence: 95%
“…The starch that is present in cereal, root and tuber crops has been extensively characterised; however, there has been little study of the characterisation of starch from avocado seeds, regarding its physicochemical properties [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%